Central venous catheter-related infections in hematology and oncology: 2020 updated guidelines on diagnosis, management, and prevention by the Infectious Diseases Working Party (AGIHO) of the German Society of Hematology and Medical Oncology (DGHO) - Böll, Boris; Schalk, Enrico; Buchheidt, Dieter; Hasenkamp, Justin; Kiehl, Michael G.; Kiderlen, Til Ramon; Kochanek, Matthias; Koldehoff, Michael; Kostrewa, Philippe Johannes; Claßen, Annika; Mellinghoff, Sibylle Christiane; Metzner, Bernd; et al. (Annals of hematology, 2021)
Cancer patients frequently require central venous catheters for therapy and parenteral nutrition and are at high risk of central venous catheter-related infections (CRIs). Moreover, CRIs prolong hospitalization, cause an excess in resource utilization and treatment cost, often delay anti-cancer treatment, and are associated with a significant increase in mortality in cancer patients. We therefore summoned a panel of experts by the Infectious Diseases Working Party (AGIHO) of the German Society of Hematology and Medical Oncology (DGHO) and updated our previous guideline on CRIs in cancer patients. After conducting systematic literature searches on PubMed, Medline, and Cochrane databases, video- and meeting-based consensus discussions were held. In the presented guideline, we summarize recommendations on definition, diagnosis, management, and prevention of CRIs in cancer patients including the grading of strength of recommendations and the respective levels of evidence. This guideline supports clinicians and researchers alike in the evidence-based decision-making in the management of CRIs in cancer patients.
Published online: 30 September 2020
Gesehen am 30.06.2021